cGAMP/Saponin Adjuvant Combination Improves Protective Response to Influenza Vaccination by Microneedle Patch in an Aged Mouse Model - Vassilieva, Elena V.; Li, Song; Korniychuk, Heorhiy; Taylor, Dahnide M.; Wang, Shelly; Prausnitz, Mark R.; Compans, Richard W. (Frontiers in Immunology, 2021)
Current strategies of improving protective response to influenza vaccines in immunosenescence do not adequately protect individuals over 65 years of age. Here, we used an aged mouse model to investigate the potential of co-delivery of influenza vaccine with the recently identified combination of a saponin-based adjuvant Quil-A and an activator of the STING pathway, 2’3 cyclic guanosine monophosphate–adenosine monophosphate (cGAMP) via dissolving skin microneedle patches (MNPs). We demonstrate that synergy between the two adjuvant components is observed after their incorporation with H1N1 vaccine into MNP as revealed by analysis of the immune responses in adult mice. Aged 21 month-old mice were found to be completely protected against live influenza challenge after vaccination with the MNPs adjuvanted with the Quil-A/cGAMP combination (5 µg each) and demonstrated significantly reduced morbidity compared to the observed responses in these mice using unadjuvanted MNPs. Analysis of the lung lysates of the surviving aged mice post challenge revealed the lowest level of residual inflammation in the adjuvanted groups. We conclude that combining influenza vaccine with a STING pathway activator and saponin-based adjuvant in MNPs is a novel option for skin vaccination of the immunosenescent population at high risk for influenza.